1998
DOI: 10.1038/sj.bmt.1701337
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of allogeneic bone marrow transplantation (BMT) on pituitary, gonad, thyroid and adrenal function in adults

Abstract: Summary:To evaluate the late-effects of allogeneic bone marrow transplantation (BMT) on endocrine function 20 adults (10 females, 10 males) with hematological malignancies were studied after a mean of 3.2 years (range 1.0-10.0) following BMT. The mean age of patients at the time of BMT was 39 years. Dynamic tests of the hypothalamicpituitary axis included growth hormone releasing hormone (GHRH), gonadotropin releasing hormone (GnRH) and thyrotropin releasing hormone (TRH) stimulations with measurements of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
16

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 26 publications
1
49
0
16
Order By: Relevance
“…28 Lower BMI were found by Nysom et al 32 in patients with childhood leukemia and lymphomas treated with TBI than in patients without TBI, which suggests that either TBI or more severe delayed side effects after HSCT alter body weight, and possibly body composition. Nyson et al 32 found that cranial irradiation leads to muscle loss and body fat in children.…”
Section: Effects Of Treatmentmentioning
confidence: 89%
See 1 more Smart Citation
“…28 Lower BMI were found by Nysom et al 32 in patients with childhood leukemia and lymphomas treated with TBI than in patients without TBI, which suggests that either TBI or more severe delayed side effects after HSCT alter body weight, and possibly body composition. Nyson et al 32 found that cranial irradiation leads to muscle loss and body fat in children.…”
Section: Effects Of Treatmentmentioning
confidence: 89%
“…It rather suggests that low LBMI is mediated by stress-related factors (treatment, infection) in the early post-BMT period, and that low LBMI in the later phases is due to a lack of muscle accretion that may be due to pituitary or hormonal dysfunction 28 and/or continued metabolic stress. 29,30 Complications noted throughout the follow-up period in our subjects included infection and sepsis, respiratory and renal insufficiency, hepatitis, chronic fatigue, depression and polyneuropathy, and these may have contributed to the lack of anabolism in the later post-HSCT period.…”
Section: Situation Before and After Hsctmentioning
confidence: 99%
“…BMI and leptin concentrations correlated positively with each other and negatively with GH peaks, but not with growth rates or plasma IGF I concentrations. Kauppila et al 18 evaluated the GH response to GH-releasing hormone in adults given BMT and also found an inverse relationship between BMI and GH peak. The persistent low BMI after TBI and the poor growth response to standard doses of GH after TBIinduced GH deficiency suggest that nutritional support may be considered to optimize the growth rate of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of hormone replacement therapy, most of them (13/14; 93%) had high serum LH and FSH levels indicating that the hypothalamus-pituitary axis was not suppressed. 26 Most often the estrogen dose used is titrated in consideration of clinical symptoms and usually this dose is thought to be high enough to prevent osteoporosis.…”
Section: Discussionmentioning
confidence: 99%